Hyperthermic Intraperitoneal Chemotherapy in Ovarian Cancer: Where Do We Go From Here? - Markman, Maurie (Oncologist, 2016)
The ongoing debate regarding a potential role for hyperthermic intraperitoneal chemotherapy in the management of ovarian cancer represents an excellent example of the rarely publicly discussed fundamental clash between the requirements of evidence-based medicine and the roles of clinical innovation and optimization of care for the individual patient.